Subjectivity and development in rural contexts - Fossa, Pablo; Serruto, Verónica (Emerald Publishing Limited, 2025)
Subjectivity and Development in Rural Contexts presents a compilation of chapters that explore different phenomena of ruralness. Through a collection of theoretical and empirical works, the book attempts to show the role of the social-cultural environment in the subjective experience and processes of human development. Psychology has historically been an urban science. However, rural psychology has experienced significant growth in recent decades. Rurality has historically been observed and analyzed through the "lenses" of the urban, sub-dimensioning its own characteristics and its psychological richness. Following a cultural approach, it can be understood that subjectivity is the result of the internalization of cultural artifacts and that it depends on the contextual frameworks in which its development takes place. Therefore, it is possible to think that ruralness has the potential to generate processes of subjectivation that are specific and typical of its social and cultural context. On the other hand, there is a need to explore development processes in rural contexts to counterbalance the urbanization of psychology taught in universities and research centers. This book brings together works from philosophy, anthropology, cultural psychology, cognitive psychology, social psychology, developmental psychology, and education. Each chapter examines the processes of subjectivation and development in rural areas. Likewise, the role of the social and cultural context in cognitive, affective, and identity development is explored. Subjectivity and Development in Rural Contexts is an invaluable resource for educators, psychologists, teachers, researchers, undergraduate and graduate students, and anyone who wants to know more about subjectivity and psychological development in ruralness.
Includes index.
Keywords: Rural conditions.; Psychology.; Psychology -- General.; Social, group or collective psychology.; elektronické knihy; electronic books